"Waiting the touch from Antarctic to ring Liberty Bell" (Miscellaneous Wire Service/Photographer, 1934)
Looking down on Mayor J. Hampton Moore, of Philadelphia,and Vice Admiral Harris Laning, U.S.N., as they stood by the Liberty Bell in Independence Hall here today (July 4th) and awaited the sounding of the famous bell by radio impulse directed from an isolated shack in Antarctica by Admiral Richard E. Byrd. Title from verso of photograph